CFD Investigation of Impact of Vessel configuration and Different Impeller Types in Stirred Tank. Issue 1 (December 2020) - Pathak, Mohit; Tamphasna Devi, Thiyam
Abstract: Computational Fluid Dynamics (CFD) study is carried out to simulate the flow characteristics of different impeller types in stirred tanks of baffled and un-baffled system. The hydrodynamic behavior induced by a Rushton turbine (RT6) and Curve Blade impeller (CD-6) is numerically analysed by solving the Navier-Stokes equations coupling with k-ε turbulence model with Multi-reference frame (MRF) impeller model. The predicted results were validated with available experimental published data and show a satisfactory agreement. The power characteristics for the two agitator systems (baffled and un-baffled) were obtained for the turbulent system of the fluid flow. In these conditions, it is found that the power number depended strongly on the length of the baffle when baffled is provided. Therefore, the presence of the baffles in the tank greatly improved the mixing performance of the system but consumes higher power than the un-baffled system. Similarly, mixing improves when Rushton impeller is employed but consumes higher power than the Curve Blade impeller. Hence, it was observed that overall efficiency of the system is better when baffled system of Curve Blade impeller is opted in any mixing operation.